REPRESENTASI ID, EGO DAN SUPEREGO DALAM LIRIK LAGU BI SARAHA KARYA ABEER NEHME: KAJIAN PSIKOANALISIS SIGMUND FREUD - Mufidah, Azahirah; Taufiq, Wildan; Restu Pauji, Resa (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study is grounded in the phenomenon of inner psychological conflict reflected in artistic works, particularly song lyrics as a medium of expression. The song Bi Ṣarāḥa by Abeer Nehme is selected due to its representation of the tension between instinctual drives and moral consciousness. This research aims to identify the representations of id, ego, and superego, and to analyze the dynamics of their interaction within the lyrics. The study employs a qualitative descriptive method using a literary psychology approach based on Sigmund Freud’s psychoanalytic theory. The data, in the form of song lyrics, are analyzed through close reading, classification, and symbolic interpretation. The findings reveal a complex interplay between the id as instinctual desire, the superego as moral control, and the ego as mediator. Their conflict constructs an inner reflection that illustrates the individual’s effort to achieve psychological balance.